A survey on face emotion recognition and applications - Muthukaruppan, Karthigayan (Association for the Advancement of Modelling and Simulation Techniques in Enterprises (AMSE), 2009)
Link to publisher's homepage at http://www.amse-modeling.org/Periodical_AMSE.html